The Analysis of Appearance of Massive Entrepreneurship Resources During Pandemic of Covid-19 in Bekasi City West Java Indonesia - Novi Hermiati (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2020)
Many entrepreneur appears in the emergence of pandemic of covid-19 in order to survive from the economic crisis.. This study aims to determine the extent of appearance of massive entrepreneurship resources during pandemic of covid-19 in bekasi city west Java Indonesia that succesfully capture the author interest. The findings of this study applied to the narrative respondents who has entrepreneurship background and lived around Bekasi City, West Java, Indonesia. The method of analysis used are qualitative data analysis: structured interview. This research conclusion give a new perspective of massive entrepreneurship resources during pandemic of covid-19 in Bekasi City, West Jawa, Indonesia exist.